Respuestas correlacionadas para el rendimiento en la seleccion de hibridos de maices precoces subtropicales - Precciado, E.=700 1 Terron, A.; Cordova, H.; Mickelson, H.; Lopez, R.
(En, Es)
ilus., 14 ref.
Keywords: ZEA MAYS; SELECCION; HIBRIDOS; GENOTIPOS; COSTA RICA